Claude Lévi-Strauss: Breaking the Spell - Paleček, Martin (Teorie vědy / Theory of Science, 2010)
When we consider which kind of theory we should apply to a given problem, one of the most important criteria is the effect of its application. In other words: we evaluate theories in terms of their abilities to solve problems. In this essay I would like to indicate which kinds of problems are crucial for social sciences and illustrate these problems by means of the structuralist criticism of functionalism. I argue that the Levi-Strauss’ proclamations about his method have never been fulfilled and that the structural anthropology is not satisfactory.